Needs Analysis Of English For Academic Purposes (Eap) For Public Sector Financial Management Students - Imran, Fathurrahman; Muhlisin, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the English for Academic Purposes (EAP) needs of students in the Public Sector Financial Management Program at the Lombok Business Academy. This study uses a mixed-methods approach with a descriptive design to obtain a comprehensive picture of students’ academic English needs. The research subjects consisted of 54 students selected using total sampling. Data were collected through questionnaires, diagnostic tests, interviews, and documentation, then analyzed using descriptive statistics and thematic analysis. The results indicate that students have high needs regarding English language skills, particularly in writing (M = 4.60), reading (M = 4.42), and speaking (M = 4.35). However, students’ actual proficiency remains in the low to moderate categories, with writing (59.8) and speaking (61.2) scores being the lowest, while reading (67.5) and listening (64.3) fall into the moderate category. Additionally, the majority of students are in the low and moderate proficiency categories (86%), while only 14% are in the high proficiency category. Students also face various challenges, such as limited vocabulary (76%), difficulty constructing academic sentences (72%), and low self-confidence in speaking (67%). The gap analysis results indicate a significant gap in writing and speaking skills. Based on these findings, English language instruction in higher education needs to be developed using an English for Academic Purposes (EAP) approach based on student needs. Instruction should be designed contextually, emphasizing academic skills, vocabulary mastery, and the use of interactive, student-centered learning methods. Thus, the development of EAP instruction is expected to optimally improve students’ English proficiency and support their academic success.